Yellowstone renewal after the fire - Ward, Jerry; Ward, Jerry (California : AIMS Multimedia)
This film explain how the 1988 fires began and spread, and how they were ultimately suppresed by an act of nature - a blanket of snow.
Production assistant, Cindy Smoot ; editor : Dale Johnson.
Narrator : Rota Cantu.
Keywords: Forest fires -- Yellowstone National Park